Fish skin grafts versus standard of care on wound healing of chronic diabetic foot ulcers: a systematic review and meta-analysis - Ruiz-Muñoz, María; Martínez-Barrios, Francisco-Javier; Cervera-Garvi, Pablo; Lópezosa-Reca, Eva; Marchena-Rodríguez, Ana José (Elsevier, 2024)
This study will explore the effectiveness of fish skin grafts (FSG) in ulcer healing in diabetic foot disease compared to standard of care (SOC). The systematic review and meta-analysis were performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standard. The electronic databases of PubMed, EMBASE, and Web of Science (WoS) internet were searched for the outcome rate of complete ulcer healing. The risk of bias assessment was conducted using the tool recommended by the Cochrane Collaboration. Statistical analysis included the individual and combined result of the studies, heterogeneity test, the effect size, sensitivity analysis, and publication bias tests. Five randomised controlled trials (RCTs) with a total of 411 patients were included in this study. This meta-analysis showed a higher rate of complete ulcer healing in groups receiving fish skin grafts (OR = 3.34, 95% CI 2.14–5.20, p < 0.01, I2 = 0%) compared to control groups. Fish skin grafts have been shown to be more effective for achieving complete ulcer healing compared to current conventional treatments in diabetic foot disease.
Keywords: Diabetes - Complicaiones y secuelas; Piel - Injertos; Fish skin grafts; Diabetic foot disease; Meta-analysis; Ulcer treatment; Randomised controlled trials